Development of Teaching Material with the Creative Problem Solving Model Using Mobile Learning Application - Aisyah Sukmafani; Munzil Munzil; Isnanik Juni Fitriyah (Universitas Negeri Malang, 2021)
This study and development aimed to produce a valid and feasible teaching material with the Creative Problem Solving (CPS) model on the activity of environmental pollution analysis using a mobile learning application in the COVID-19 pandemic era. The study model in this development was using the ADDIE method that limited to analyze, design, and develop stages where each stage passes the evaluation stage. The validity rate of the teaching material is obtained through a validity test by the validator while its eligibility rate is obtained through feasibility tests by the users. The validation result of materials in the teaching material had a percentage of 93.31 percent and the media feasibility test obtained a percentage of 95.60 percent. This teaching material was packed in a mobile learning form that consists of water, air, and land pollution materials. This teaching material displayed news articles, materials explanations, and presented in the form of animated videos, phenomena videos, pictures of environmental pollution, student worksheets, and mission-based learning activities. Animated videos have three animation characters that move and talk with different voices in each sub-chapter. The validation result by validators stated that the teaching material is valid and feasible, with a percentage of greater than or equal to 81 percent.